1998
DOI: 10.1046/j.1365-8711.1998.01706.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the optical-radio correlations for powerful radio galaxies

Abstract: A B S T R A C TThe nature of the optical-radio correlations for powerful radio galaxies is investigated using spectroscopic observations of a complete sample of southern 2-Jy radio sources. In line with previous work, we find that significant correlations exist between the luminosities of the [O III]l5007, [O II]l3727 and Hb emission lines and the radio luminosity. However, our observations are not easily reconciled with the idea that these correlations are caused by the increase in the power of the photoioniz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
235
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(251 citation statements)
references
References 40 publications
15
235
1
Order By: Relevance
“…In NVSS J004000−303333 we find two very faint unresolved continuum emitters of about equal flux, perhaps indicating an ongoing interaction of two galaxies, or AGN light scattered on extended dust (e.g., Hatch et al 2009). Both blobs are roughly along the radio jet axis, somewhat reminiscent of the alignment effect found in more powerful HzRGs (Tadhunter et al 1998;Vernet et al 2001). In NVSS J234235−384526 we do not detect the continuum at all.…”
Section: Rest-frame Optical Continuummentioning
confidence: 55%
See 1 more Smart Citation
“…In NVSS J004000−303333 we find two very faint unresolved continuum emitters of about equal flux, perhaps indicating an ongoing interaction of two galaxies, or AGN light scattered on extended dust (e.g., Hatch et al 2009). Both blobs are roughly along the radio jet axis, somewhat reminiscent of the alignment effect found in more powerful HzRGs (Tadhunter et al 1998;Vernet et al 2001). In NVSS J234235−384526 we do not detect the continuum at all.…”
Section: Rest-frame Optical Continuummentioning
confidence: 55%
“…Whereas the jets of powerful radio galaxies in the local Universe are known to affect the gas locally within extended gas disks ("jet-cloud interactions", e.g., Tadhunter et al 1998;van Breugel et al 1985), it was found only recently that outflows driven by the most powerful radio jets in the early universe at z ∼ 2 can encompass very high gas masses, up to about 10 10 M in the most powerful radio galaxies at high redshift (Nesvadba et al 2006(Nesvadba et al , 2008a. This is similar to the typical total gas masses in massive, intensely star-forming, high-redshift galaxies of a few 10 10 M (e.g., Greve et al 2005;Tacconi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…5). In this sense it is similar to the WLRG, that are defined to have small [OIII]λ5007 emission line equivalent widths (EW [OIII] < 10 Å, see Tadhunter et al 1998). However, in contrast to the other WLRG in the 2 Jy sample, our previous spectroscopic investigation of PKS 1814-637 (see Holt et al 2008) suggested a higher equivalent width and classification as a NLRG.…”
Section: Optical Spectral Classificationmentioning
confidence: 86%
“…This work was originally motivated in part by the desire to find the first powerful radio galaxies, at very high redshifts (z>5; van Breugel et al 1999). While LDRRGs have been proposed as candidates for very high redshift radio galaxies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They are hosted by massive elliptical galaxies or their progenitors, and can be detected across a vast range in redshift (z∼0 to z>5: e.g. van Breugel et al 1999). In observing a powerful radio galaxy we get to see a massive galaxy as it undergoes a phase of significant accretion of matter onto its supermassive black hole, the radiative and mechanical output from which can potentially affect the subsequent stellar mass assembly activity and the gaseous properties of the galaxy.…”
Section: Introductionmentioning
confidence: 99%